THE EFFECT OF LAVENDER OIL IN RELIEVING PERINEAL PAIN FOLLOWING CHILDBIRTH - Agus, Yenita; Ikrowardani, Septiara; Elsa, Nadhia (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Postpartum mothers often face discomforts such as back pain, uterine cramps, fatigue, and perineal pain. Perineal pain after an episiotomy can significantly impact daily activities, maternal quality of life, and the mother-infant relationship. Effective management is crucial to decrease the perineal pain. Objectives: The study aimed to evaluate the effect of lavender oil on relieving perineal pain in postpartum mothers. Methods: A pre-experimental design with a pretest-posttest format was used. Participants, selected through purposive sampling, were assessed for pain intensity using a Numeric Rating Scale (NRS) from 0 to 10. Bivariate analysis was conducted using the Wilcoxon test to assess changes in pain levels before and after the intervention. Results: The significance level was found to be 0.004 (p < 0.05), indicating a statistically significant reduction in pain intensity. Conclusion: Lavender oil aromatherapy effectively reduces perineal pain in postpartum mothers. Although the study lacked a control group, lavender oil was found to be a safe and effective treatment, with no reported side effects.